Heroes among community: Universiti Utara Malaysia social responsibility builds sustainable and Developed Youngsters - Nurul Aminah Kamarudin; Faeiq Shauqy Kareem Semmard (Penerbit Universiti Kebangsaan Malaysia, 2024)
In Malaysia, all higher education institutions are obliged to promote community engagement among the students. A community engagement programme is any individual or organisation willing to run an activity or programme that will help their local community. This community engagement should be widened and enlarged throughout the youth, especially students, to ensure that society is well-developed and sustainable. This project aims to help youngsters build their character through community-based activities and interactions. A quantitative methodology was employed to survey university students and assess the impact of community engagement programs on their development. Descriptive statistical analysis methods, such as frequencies and percentages, were used to evaluate the data collected through a Google Forms survey. This analysis provided a detailed overview of the demographics, motivations, and challenges reported by UUM students, with the data presented in tables, graphs, and charts. The findings indicate that UUM students frequently participate in community service activities that benefit the local community, enhance community members' lives, and contribute to their well-being through student involvement. For example, the Student Leadership and Development Committee Bank Rakyat Residential Hall organised the 'University Social Responsibility: Tautan Kasih, Sentuhan Jiwa Bersama' program in Kampung Gadong Jaya, Labu, Negeri Sembilan. This program aimed to allow the committee members to improve their interpersonal skills by engaging with villagers and an NGO in cooking activity, preparing Negeri Sembilan specialties such as Rendang Ayam and Ayam Masak Lemak Cili Api. The students interacted with locals at the Pusat Aktiviti Warga Emas (PAWE) hall and donated to disadvantaged community members. Such involvement and outreach initiatives can foster creative thinking and originate from the students' initiative.